ACADEMIC PROCRASTINATION: A NARRATIVE STUDY BASED ON THE PERSPECTIVE OF GRADE XI STUDENTS IN A SCHOOLS IN MADIUN - Agung Dwi; Fakhruddin Mutakin; Yurike Kinanthy Karamoy (Universitas Negeri Surabaya, 2025)
Academic procrastination, which is often defined as delaying work on assignments, it is believed that every students has exposure that feeling. This study used qualitative research whose participants were class XI vocational school students whose opinions became the basis for this research. The criteria for research participants used purposive sampling (Jupp, 2006) and for participant recruitment, researchers followed the ethical procedures recommended by Hammersley & Traianou, (2012). Besides that, this research uses narrative studies (Connelly & Clandinin, 1990), stories as a data source, and interviews (Barkhuizen et al., 2014) to collect data and in the process use thematic analysis (Braun & Clarke, 2008). To test the level of trust, researcher use the theory of peer debriefing (Janesick, 2015) and member checking (Lincoln & Guba, 1985). As a results, there are several things, both intrinsic and extrinsic, that influence a person to carry out procrastination behavior. Regarding gender, this behavior has no predisposition, everyone can do this behavior. Keywords: Academic Procrastination, Narrative Study, Purposive Sampling, Qualitative Research, , Thematic Analysis